Collaborative modelling‐based shelter planning analysis: a case study of the Nagata Elementary School Community in Kobe City, Japan. Issue 1 (January 2014) - Xu, Wei; Li, Ying; Okada, Norio; Takeuchi, Yukiko; Kajitani, Yoshio; Shi, Peijun
<x xml:space="preserve">Abstract</x> This study, based on a questionnaire survey and workshops, and with a focus on the impact of an earthquake on the Nagata Elementary School Community in Kobe City, Japan, develops a collaborative model to assess the allocation of residents to shelters. The current official allocation plan is compared with three alternative allocations developed within the framework of this model. The collaborative model identifies accessibility, amenity, capacity, connectivity, continuity, security, and stability as the basic, necessary criteria for shelter planning. The three alternative allocations are very similar to the local residents' own choice of shelters, but they are quite different from the current official allocation plan, which is supposed to be followed but has achieved relatively low satisfaction among households. The proposed collaborative approach provides an effective tool to assess the officially determined allocation plan by taking into account the viewpoints of local residents, and the results are useful for enhancing community evacuation planning.